PELANGGARAN KODE ETIK : Pelanggaran Kode Etik Yang Dilakukan Oleh Anwar Usman Selaku Ketua Mahkamah Konstitusi - Bintang D; Mela Roido B S; Ghasela Julianna A (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2023)
The Constitutional Court in Indonesia plays a crucial role in overseeing the constitution and making decisions at the first and final levels. However, its authority is not always exercised in line with regulations and procedures. This paper discusses the importance of management ethics in the context of an ethics violation case involving Anwar Usman, the Chief Justice of the Constitutional Court. Anwar Usman's violation of the code of ethics has serious implications for the institution's integrity and public trust. The interconnection between management, ethics, and the case of ethical violations is explored to evaluate how ethics influences public trust